2020
DOI: 10.1017/s0022377820000860
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation dynamo in a weakly collisional plasma

Abstract: The turbulent amplification of cosmic magnetic fields depends upon the material properties of the host plasma. In many hot, dilute astrophysical systems, such as the intracluster medium (ICM) of galaxy clusters, the rarity of particle–particle collisions allows departures from local thermodynamic equilibrium. These departures – pressure anisotropies – exert anisotropic viscous stresses on the plasma motions that inhibit their ability to stretch magnetic-field lines. We present an extensive numerical study of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 93 publications
(205 reference statements)
5
37
0
Order By: Relevance
“…This may also be a step towards simulations becoming more consistent with Faraday-rotation observations of magnetic fields in galaxy clusters suggesting kpc-scale coherence [61,62], as well as recent laboratory laser-plasma experiments exhibiting a Pm 1 fluctuation dynamo [63,64]. Determining whether or not this result holds when using the pressure-anisotropic MHD [39,65] or kinetic [66,67] descriptions more appropriate to the weakly collisional intracluster medium awaits future work.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This may also be a step towards simulations becoming more consistent with Faraday-rotation observations of magnetic fields in galaxy clusters suggesting kpc-scale coherence [61,62], as well as recent laboratory laser-plasma experiments exhibiting a Pm 1 fluctuation dynamo [63,64]. Determining whether or not this result holds when using the pressure-anisotropic MHD [39,65] or kinetic [66,67] descriptions more appropriate to the weakly collisional intracluster medium awaits future work.…”
Section: Discussionmentioning
confidence: 85%
“…Once the mean magnetic energy becomes comparable to the energy of the viscous-scale motions (viz., B 2 rms ∼ U 2 Re −1/2 ), the kinematic stage ends and the dynamo becomes nonlinear. Namely, the Lorentz force due to the spatially coherent magnetic folds back-reacts on the viscous-scale motions and suppresses their ability to amplify the magnetic field [17,[33][34][35][36][37][38][39]. As a result, progressively larger (and slower) eddies are responsible for amplifying the field, while the eddies whose energies are lower,…”
Section: A Generation and Persistence Of Magnetic Foldsmentioning
confidence: 99%
“…This would be the case when hard-coded "anisotropy limiters" are employed to bound the values of the pressure anisotropy within a physically "sensible" range, something usually adopted when modeling (nearly) collisionless plasmas as fluids. For example, to mimic microphysical instabilities that "feed" on the pressure anisotropy, limiters were added to collisionless MHD-like models to perform numerical studies of magneto-rotational instability (Sharma et al 2006), to perform numerical studies of the turbulent dynamo in the intracluster medium (Santos-Lima et al 2014;St-Onge et al 2020), and to derive a heating mechanism able to stably balance radiative cooling in the central regions of cold-core clusters of galaxies (Kunz et al 2011). In all these examples the inclusion (via the limiters) of microphysical effects significantly changes the saturation level of macroscopic quantities.…”
Section: Hvlf: Landau-fluid Electronsmentioning
confidence: 99%
“…𝑘 rms measures the overall variation of magnetic fields. For a subsonic fluctuation dynamo with Pm 1, it is shown that the magnetic field organises itself into folded structures [42,68]. Furthermore, the structures are folded sheets in the kinematic stage (identified by the condition, 𝑘 𝑘 b•j 𝑘 b×j ∼ 𝑘 rms ) and folded ribbons in the saturated stage (identified by the condition, 𝑘 𝑘 b•j 𝑘 b×j ∼ 𝑘 rms ).…”
Section: B Characteristic Magnetic Scalesmentioning
confidence: 99%